WORKSHOP PENGELOLAAN PEMBELAJARAN JARAK JAUH (PJJ) BERBASIS LEARNING MANAGEMENT SYSTEM (LMS) BAGI GURU SMKN 1 JETIS MOJOKERTO - Eko Sugandi; Nur Fathonah; Erna Puji Astutik; Liknik Nugraheni (STKIP PGRI Sidoarjo, 2021)
The Covid-19 epidemic has triggered technological upheavals that are occurring rapidly in all areas of life, including the world of education. Technology is an alternative that can be used extensively by teachers in the teaching and learning process. The limited knowledge of technology of teachers in schools is a serious problem and a solution must be provided immediately in order to create an interesting, effective and innovative learning atmosphere so that the pupils can still fully understand the material even if it is done. virtually. The Mathematics Education Curriculum is conducting a Community Service Program (PPM) with SMKN target partner 1 Jetis Mojokerto. The majority of teachers in the school have limited knowledge of Distance Learning Management (PJJ) based on the Learning Management System (LMS) during the COVID-19 pandemic. The learning process emphasizes the use of Whatsapp media and only a small number of teachers use LMS with very simple content presentation. Thus, the PPM program is carried out with the aim of helping teachers to manage distance learning (PJJ) based on the learning management system (LMS) of Google Classroom. The PPM program has three stages, namely the planning stage, the socialization stage and the implementation stage. Teachers are very enthusiastic in the online workshop activities and show positive results after participating in activities based on the results of filling in online questionnaires, the majority of whom think the material presented is very useful and the activities offline workshops can be conducted continuously.